2019
DOI: 10.3390/app9235019
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Effect of Active Modified Atmosphere Packaging on the Microbial Stability and Shelf Life of Gutted Sea Bass

Abstract: The aim of the study was the evaluation and mathematical modeling of the effect of active modified atmosphere packaging (MAP), by the incorporation of CO2 emitters in the package, on the microbial stability and shelf life of gutted sea bass during refrigerated storage. Gutted sea bass samples were packaged in modified atmosphere (50% CO2–40% N2–10% O2) with and without CO2 emitters (ACT-MAP, MAP) (gas/product volume ratio 3:1) and stored at isothermal conditions: 0 °C, 5 °C, and 10 °C. The gas concentration in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 44 publications
2
12
0
Order By: Relevance
“…Hansen et al (2016) compared packaging of Atlantic cod in vacuum or MA packaging, with or without a CO 2 emitter, and found that inclusion of the emitter significantly decreased bacterial growth and prolonged sensory shelf life from 7 to 13 days. This agrees with Hansen et al (2007), Hansen, Mørkøre, Rudi, Rødbotten, et al (2009), andTsironi et al (2019). More importantly, the latter studies obtained increased shelf life, despite lowering the g/p ratio considerably, from 4:1 to 1.3:1 and 3:1 to 1:1, respectively (Hansen et al, 2007;Hansen, Mørkøre, Rudi, Rødbotten, et al, 2009).…”
Section: Gaseous Packaging Methodssupporting
confidence: 83%
See 1 more Smart Citation
“…Hansen et al (2016) compared packaging of Atlantic cod in vacuum or MA packaging, with or without a CO 2 emitter, and found that inclusion of the emitter significantly decreased bacterial growth and prolonged sensory shelf life from 7 to 13 days. This agrees with Hansen et al (2007), Hansen, Mørkøre, Rudi, Rødbotten, et al (2009), andTsironi et al (2019). More importantly, the latter studies obtained increased shelf life, despite lowering the g/p ratio considerably, from 4:1 to 1.3:1 and 3:1 to 1:1, respectively (Hansen et al, 2007;Hansen, Mørkøre, Rudi, Rødbotten, et al, 2009).…”
Section: Gaseous Packaging Methodssupporting
confidence: 83%
“…(2009), and Tsironi et al. (2019). More importantly, the latter studies obtained increased shelf life, despite lowering the g/p ratio considerably, from 4:1 to 1.3:1 and 3:1 to 1:1, respectively (Hansen et al., 2007; Hansen, Mørkøre, Rudi, Rødbotten, et al., 2009).…”
Section: Mild Processing Methods For Seafoodmentioning
confidence: 97%
“…Some studies found that higher CO 2 contents in packaging atmosphere were more effective in inhibiting bacterial growth and retarding biochemical changes (Olatunde, Benjakul, & Vongkamjan, 2020; Yew et al., 2014). A timely supplement to CO 2 absorbed by food matrixes could also be beneficial for improving the preservative effect (Tsironi et al., 2019). As for common spoilage bacteria in air‐packed fishery products, Aeromonas and Shewanella are usually more resistant to CO 2 than Pseudomonas and can keep slow growth in MAP conditions (Antunes‐Rohling, Artaiz, et al., 2019; Jakobsen, Shumilina, Lied, & Hoel, 2020; Zhang et al., 2019).…”
Section: Influencing Factors Of Microbiota Composition In Fish and Crmentioning
confidence: 99%
“…Despite the advantages of MAP, it is space-demanding, as a high-gas volume/product volume ratio (g/p) is needed in order to preserve the high quality of fish products. However, the concentration of CO 2 within the package will change due to the partial dissolution of CO 2 into the product and permeability through the packaging film [ 8 , 9 ]. The use of CO 2 emitters (pads) inside the modified atmosphere packaging can be viewed as a technique complimentary to MAP to overcome the drawbacks.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon dioxide emitters utilizing the O 2 in the package headspace produce CO 2 , thus enhancing the concentration of CO 2 /N 2 inside the package headspace without needing an initial high CO 2 concentration. The addition of CO 2 emitters in the bottom of the tray can compensate for an initial low g/p ratio after sealing the package, thereby preventing the requirement of an initial high g/p and the deformation of the package during storage [ 3 , 8 , 9 ]. Moreover, these pads produce CO 2 when they come into contact with the water leaked from the food matrix; thus, they may also simultaneously act as liquid absorbers [ 7 ].…”
Section: Introductionmentioning
confidence: 99%